New two in one magnetic fluorescent nanocomposites - VENKATESAN, MUNUSWAMY; GOUNKO, IOURI (SPIE, 2005)
Magnetite nanoparticles have been coated by a porphyrin derivative to produce new magnetic materials with fluorescent properties. The magnetic nanoparticles were prepared using two different methods, one based on sol-gel techniques and ultrasonic processing, and the other via a controlled chemical co-precipitation. Different types of porphyrin functionalised magnetic nanoparticles have been prepared and have been characterised by electron microscopy (TEM and SEM), XRD, FTIR, Raman, UV-vis, and fluorescence spectroscopy. Microscopy results showed the formation of core-shell nanostructures, with IR and photoluminescence spectroscopy results confirming the presence of porphyrin in the shell.
PUBLISHED
Keywords: Chemistry